2005
DOI: 10.1242/jcs.02362
|View full text |Cite
|
Sign up to set email alerts
|

SYCP2 and SYCP3 are required for cohesin core integrity at diplotene but not for centromere cohesion at the first meiotic division

Abstract: Much of the organization of the meiotic prophase-I chromosome axis is attributed to two groups of proteins: the axial element proteins, SYCP2 and SYCP3; and the cohesin-complex proteins. Although the cohesin-complex proteins ensure that sister chromatids remain paired during meiosis, the role of SYCP2 and SYCP3 is not clear. Interestingly, it has been shown that SYCP3 and SYCP2 associate with the centromere regions of male, but not female, metaphase-I chromosomes, suggesting a sex-specific function for the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 35 publications
(45 reference statements)
3
94
1
Order By: Relevance
“…Alternatively, our results may be consistent with the Kim et al (2010) finding that in later stages of recombination, yeast Rec8 acts to enforce IH bias. Kouznetsova et al (2005) observed that the lateral axis SC structure in Sycp3 2/2 oocytes has discontinuities in staining for cohesins including STAG3 and REC8. These local disruptions of the cohesin complex may compromise IH bias.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Alternatively, our results may be consistent with the Kim et al (2010) finding that in later stages of recombination, yeast Rec8 acts to enforce IH bias. Kouznetsova et al (2005) observed that the lateral axis SC structure in Sycp3 2/2 oocytes has discontinuities in staining for cohesins including STAG3 and REC8. These local disruptions of the cohesin complex may compromise IH bias.…”
Section: Discussionmentioning
confidence: 90%
“…Sycp3 2/2 may reflect a general role for the SC in partner choice/BSCR function. Supportive of this possibility is that although axial elements form on pachytene chromosomes of SYCP3-deficient oocytes, they are abnormal and have discontinuities in the axis structure (Kouznetsova et al 2005). If the axial element itself is governing partner choice, this would predict that deletion of other axial element components would have similar effects.…”
Section: Resultsmentioning
confidence: 99%
“…RPA is then replaced by RAD51, with the aid of mediators such as also important for correct homologous chromosome pairing and crossover formation. [12][13][14] For example, in male Sycp3 knockout mice, many chromosomes remain asynapsed or show heterologous synapsis, and the spermatocytes become apoptotic around the developmental phase that corresponds to midpachytene in wild type, the stage at which all autosomal chromosomes should have achieved complete synapsis. 12 Many mutants that have pairing and DSB repair abnormalities, show asynapsis at pachytene, resulting in apoptosis around this stage.…”
Section: Introductionmentioning
confidence: 99%
“…In general, ATM appears to be rapidly recruited to DSB sites, followed by later accumulation of ATR. Conversely, large 13 1 bivalent. The small translocation bivalent shows complete synapsis in only 40% of the nuclei, whereas the larger bivalent is completely synapsed in more then 95% of the nuclei.…”
mentioning
confidence: 99%
See 1 more Smart Citation